Vocational rehabilitation in multiple sclerosis (MS): a profile of clients seeking services. - Fraser RT; Johnson EK; Clemmons DC; Getter A; Johnson KL; Gibbons L (Work, 2003)
Although a number of innovative vocational rehabilitation (VR) demonstration projects have been completed with MS populations, there remains a lack of clarity as to a profile of these VR participants. An effort is made in this article to carefully describe the demographic and occupational characteristics of people with MS seeking vocational services at intake, as well as their self-perceived psychosocial functioning across a range of pertinent measures. The issue of 'program dropouts' in VR services for people with MS is also addressed. Implications for better understanding participants with MS within the VR process and improved nuances in service delivery are then discussed.